A study on knowledge and attitude of different level of education regarding biotechnology application in Malacca / Mohd Nazli Ayub - Ayub, Mohd Nazli Ayub (Faculty of Plantation and Agrotechnology, 2015)
Biotechnology is one of the five cores technologies that will drive the transformation of Malaysia into a leading industrial country by 2020. According to the theory of decision-makers, one has only to shape attitudes toward technology and applications after they receive the relevant information. Therefore it is important to assess the knowledge and attitudes of students towards biotechnological applications. Today's students must be alert with the risks and benefits of biotechnology to make intelligent decisions about science are for them and future generations. The purpose of this survey is to assess the knowledge and attitudes of djfferent education levels in Melaka for biotechnological applications. A survey was conducted 011 176 respondents from different educational levels students from secondary school, diploma I integral / matriculation / pre-university, undergraduate and master and higher. The results showed an overall mean score for knowledge of biotechnology applications in which high school is the highest in comparison with the level of education among others. This is a surprising result because it is expected the master level knowledge of biotechnology applications have the higher awareness. In addition, positive reaction showed in the attitudes towards biotechnology application. ANOVA was used to show the different between knowledge and attitudes of the different levels of education to biotechnology applications.